Synthesis, characterizations and biological properties of some hydrazones and their metal complexes / Siti Munirah Saharin - Siti Munirah, Saharin (2012)
The aim of the project as presented in this thesis concerns on the preparation, characterization and biological evaluation of Schiff bases derived from 3, 5- dihyroxybenzohydrazide and their Cu(II) and Zn(II) complexes. The Schiff bases were synthesized by the condensation of 3, 5-dihyroxybenzohydrazide and hydroxyacetophenone (BzyHAP-H), 5-bromo hydroxyacetophenone (BzyHAP-Br), 5- chloro hydroxyacetophenone (BzyHAP-Cl), salicylaldehyde (BzySAL-H), 5-bromo salicylaldehyde (BzySAL-Br), and 5-chloro salicylaldehyde (BzySAL-Cl). The BzyHAP series ligands were subsequently reacted with the acetate of Zn(II) whereas the BzySAL series ligands were reacted with Cu(II) and Zn(II) acetate in a 1:2 metal to ligand ratio. The chemical structures of the compounds were characterized by means of elemental analyses, , and spectroscopy methods including IR, 1H NMR, 13C NMR, and UV-Vis.The determination of metal content was carried out using atomic absorption spectroscopy. Single X-ray diffraction data collection is carried out for ligand BzySAL-Br. From the structural analysis, the ligand is found to be planar with an r.m.s. deviation for the non-H atoms of 0.16Å. In the crystal structure, the Schiff base molecules and the water molecules are linked together by intermolecular N-H--O and O-H--O hydrogen bonds, leading to layers parallel to the bc plane. An intramolecular O-H--N hydrogen bond involving the imine N atom and a hydroxyl substituent is also observed. The synthesized Schiff base and their metal complexes are screened for the in vitro cytotoxicity towards prostate cancer cell line (PC-3), colon cancer cell line (HT-29) lung cancer cell line (A549), and normal cell line (WRL-68). All Zn (II) complex Schiff bases show relatively low cytotoxicity against all tested cell line. Complexes labeled as CuBzySAL-H, CuBzySAL-Br, and CuBzySALCl show encouraging value of EC50 against colon cancer cell line (HT-29), lung cancer cell line (A549), and normal cell line (WRL-68). On contrary, the cytotoxicity against prostate cancer cell line (PC-3) is recorded negative. The evaluation of antioxidant reveals that all compounds are moderate DPPH inhibitor compared to the standard vitamin C.